A Chalcedonic Die of Astynomos ῾Ηράκλειος from Tauric Chersonesus - Novoselova, Nadezhda; Namoylik, Anna (Hyperboreus, 2019)
In 2018, a chalcedonic die was discovered in ﬁlling of a cellar of the Hellenistic house in the Quarter XX of Tauric Chersonesus. It bears an inscription ἀστυνομοῦ-|ντος ῾Ηρακ-|λείου (‘Herakleios being astynomos’) and two emblems – a bunch of grapes and a caduceus. Palaeographic peculiarities of the inscription as well as archaeological context of the ﬁnd point to the date of the late 4th – early 3rd century BC. Astynomoi named ῾Ηράκλειος are known from stamps on Chersonesan amphorae, however no stamp imprinted by the die under discussion has been found. This tool might have been intended for sealing documents. The unique ﬁnd supplements scarce evidence on the board of astynomoi making us revise a traditional view that it was a low-status magistracy in Chersonesus.